Faith and palliative care: a partnership of care in low- and middle-income countries. Issue 5 (4th July 2017) - Grant, Elizabeth; Leng, Mhoira; Namukwaya, Elizabeth; Onapito, Ivan Odiit; Kimani, Kellen; Downing, Julia
ABSTRACT: The provision of holistic palliative care has been identified by WHO as a human right, important for all people, at all ages, with all life-limiting illnesses. When faced with death and dying, issues of meaning and relationships with others, the world, and with the sacred are intensified even more in communities where faith and spiritual beliefs have a significant place. Being able to understand the significance of dying and interpreting the experience and period of living with life-limiting illness, presents an important challenge for palliative care. This article sets out the contribution that faith communities have made in understanding the significance of spiritual issues in health and in delivering palliative care in lower to middle-income contexts where palliative care has been prioritised.